The Precarious State of Letter C: Land Registration Law Dynamics After PP Number 18 Year 2021 - Naning indriyawati; Suyanto Suyanto; Dara Puspitasari (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The enactment of Government Regulation (PP) No. 18 of 2021 has triggered a major transformation in Indonesia’s land registration framework. The primary focus of this study is to evaluate the current legal status of "Letter C" and determine whether it still functions as robust evidence of ownership or merely as proof of physical possession. Under the latest regulations, the role of Letter C has undergone a significant shift, moving from a primary form of evidence to a transitional or temporary document within the national land registration process. This study employs a normative legal research method, examining various regulatory layers, including the Basic Agrarian Law (UUPA) No. 5 of 1960, the Job Creation Law No. 11 of 2020, and specific provisions in PP No. 18 of 2021 regarding mandatory land registration. Furthermore, a conceptual approach is used to compare the administrative weight of Letter C against the absolute legal certainty provided by a formal land certificate. Data was gathered through an analysis of legal documents from the BPN Legal Documentation and Information Network (JDIH), agrarian law journals, and court rulings involving customary land disputes. The analysis reveals that after 2026, Letter C documents will hold a very weak legal position if they are not promptly converted through the Complete Systematic Land Registration (PTSL) program. From a legal standpoint, Letter C is now classified only as a temporary basis of right (alas hak) that requires re-verification by Land Deed Officials (PPAT) and the National Land Agency (BPN). To address this vulnerability, it is recommended that the government provide subsidies for verification costs and conduct extensive public outreach to ensure legal certainty and agrarian justice for the community.